Does free public transit increase physical activity and independent mobility in children? Study protocol for comparing children's activity between two Finnish towns with and without free public transit - Arto J. Pesola; Pirjo Hakala; Päivi Berg; Samira Ramezani; Karen Villanueva; Sari Tuuva-Hongisto; Jussi Ronkainen; Tiina E. Laatikainen (BMC, 2020)
Abstract Background Children's habitual physical activity, including active travel and catching public transit (walking and cycling to and from destinations), and independent mobility (mobility without an adult) have decreased. Public transit trips are physically active and can provide access to hobbies independent of parents, but there is no device-measured data about children's total physical activity time following the introduction of free public transit. Our aim is to compare physical activity and independent mobility between children living in two Finnish towns, one with a recently introduced free public transit system, and the other without free public transit. Methods The city of Mikkeli has provided free public transit for all comprehensive school children since 2017. Various districts from Mikkeli, and the reference town of Kouvola (towns from South-Eastern Finland with a comparative population size and geographical structure), are selected based on their accessibility and the availability of public transit services. Samples of 10-12-year-old children will be recruited through primary schools. We will compare moderate-to-vigorous physical activity time, sitting time (a thigh-worn Fibion® device) and independent mobility (a participatory mapping method, PPGIS) of children: 1) who live in towns with and without free public transit, 2) who live and go to school in districts with high vs. low perceived and objective access to free public transit, and 3) who report using vs. not using free public transit. In addition, ethnography will be used to get insights on the social and cultural effects of the free public transit on children's and parent's everyday life. Discussion There is a need for scalable solutions that can increase children's physical activity independent of their socioeconomic background or place of residence. This project will give information on how a political action to provide free public transit for children is associated with their total physical activity time and independent mobility patterns, therefore providing highly relevant information for political decision-making and for promoting independent physical activity in children.